Gamification as a tool for learning and assessment of soft skills at school - Natalia Altomari; Antonella Valenti (Firenze University Press, 2023)
Learning and assessing new skills is a challenge in education that teachers must take up primarily, playing a key role in the educational success of each student. With this perspective, soft skills (or transversal skills) are often considered of secondary importance, instead, if developed properly, they are among the skills required in the world of work, as well as in the purely educational world. Such skills, activated and enhanced through an innovative tool such as gamification, could be an answer to this gap. Serious games, in fact, are not only a means of entertainment or playfulness but are increasingly finding their place in the educational field.   La gamification come strumento di apprendimento e di valutazione delle competenze trasversali a scuola. L'apprendimento e la valutazione di nuove abilità rappresentano una sfida nel settore educativo che deve essere colta principalmente dai docenti, giocando, questi, un ruolo fondamentale nel successo formativo di ciascuno studente. In quest'ottica, le soft skills (o abilità trasversali) vengono spesso considerate di secondaria importanza, invece, se sviluppate adeguatamente, rientrano tra le competenze richieste nel mondo del lavoro, oltre che in quello prettamente scolastico. Tali abilità, attivate e potenziate attraverso uno strumento innovativo quale la gamification, potrebbero rappresentare una risposta a questa lacuna. I serious game, infatti, non sono solo un mezzo di intrattenimento o ludico ma trovano sempre più spazio in ambito educativo.